Site specificity of mechanical and structural properties of human fascia lata and their gender differences: A cadaveric study. (22nd August 2018) - Otsuka, Shun; Yakura, Tomiko; Ohmichi, Yusuke; Ohmichi, Mika; Naito, Munekazu; Nakano, Takashi; Kawakami, Yasuo
Abstract: The whole thigh muscles are covered with the fascia lata, which could have morphological and mechanical features that match the underlying muscles' functions. In this study, we investigated the morphological and elastic properties of the human fascia lata taken from four (anterior, medial, lateral, and posterior) sites on the thigh of 17 legs of 12 cadavers (6 males and 6 females, 75–92 years). The thickness of the fascia lata was determined with a caliper. The interwoven collagen fiber's directions were measured and classified into longitudinal, transverse, and diagonal in two opposing directions, relative to the thigh. Tensile strength test along the longitudinal and transverse directions was performed, and the stiffness, Young's modulus, and hysteresis were determined. Fascia lata at the lateral site (0.8 ± 0.2 mm) was significantly thicker compared to other sites (0.2–0.3 mm). Fiber's directions showed substantial variability among sites, and longitudinally directed fibers were higher in proportion (28–32%) than those in other directions (20–27%) at all sites except for the posterior site. The stiffness and Young's modulus in the longitudinal direction (20–283 N/mm; 71.6–275.9 MPa, highest at the lateral site) were significantly higher than in the transverse direction (3–16 N/mm; 3.2–41.9 MPa, lowest at the lateral site). At the medial site, the proportion of the transversely directed fibers was higher in females than males, with higher stiffness and Young's modulus thereof. The present study shows that the fascia lata possesses site- and gender-dependence of the morphological characteristics and elastic properties.